2015
DOI: 10.1148/rg.2015140110
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis below the Diaphragm: Abdominal Findings in Adult Patients

Abstract: Cystic fibrosis (CF) is the most common lethal autosomal recessive disease in the white population. Mutation of the CF transmembrane conductance regulator gene on chromosome 7 results in production of abnormally viscous mucus and secretions in the lungs of patients with CF. A similar pathologic process occurs in the gastrointestinal tract, pancreas, and hepatobiliary system. Inspissated mucus causes luminal obstruction and resultant clinical and radiologic complications associated with the disease process. Pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 62 publications
0
35
1
1
Order By: Relevance
“…Thus, acute appendicitis may be atypical. Symptoms may be confusing with DIOS and intussusception or the results may be masked by a prescribed antibiotic therapy to prevent pulmonary exacerbation [2]. Coughlin et al reported 60% of the classical symptoms of appendicitis in the general population against only 45% in CF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, acute appendicitis may be atypical. Symptoms may be confusing with DIOS and intussusception or the results may be masked by a prescribed antibiotic therapy to prevent pulmonary exacerbation [2]. Coughlin et al reported 60% of the classical symptoms of appendicitis in the general population against only 45% in CF.…”
Section: Discussionmentioning
confidence: 99%
“…When gastrointestinal system is affected, abdominal pain is the most common symptom in patients with CF and is frequently due to distal ileal obstruction syndrome (DIOS). Other conditions which are leading to lower abdominal pain in these patients are intussusception, volvulus, pancreatitis and fecaloma [2]. Acute appendicitis is a rare entity in CF [3].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis is typically made via ultrasound or CT, with the classic "doughnut" or "target" sign. 103 The first-line treatment is contrast enema, which can be both diagnostic and therapeutic. Exploratory laparotomy may be necessary if enema fails or intussusception is persistent, but when associated with CF, surgical intervention is often not necessary.…”
Section: Intussusceptionmentioning
confidence: 99%
“…23,34 The etiology of DIOS is thought to be related to a delayed transit of thickened secretions in the lumen of the gastrointestinal tract. 12 It has been proposed that pancreatic insufficiency leads to high fecal fat, which increases stool viscosity and activates the ileal break, delaying transit of intraluminal con-tents. 23 The ileal break is a feedback loop that is activated by fat in the ileum and slows jejunal motility, delays gastric emptying, and reduces small intestinal transit of solid and liquid intraluminal contents.…”
Section: Long-term Complications (Distal Intestinal Obstruction Syndrmentioning
confidence: 99%